An An Exploration Of Icebreakers And Their Impact On Student Engagement In The Classroom - john Michael V Sasan; Gica M. Tugbong; Kent Lancer C. Alistre (Ridwan Institute, 2023)
This study examined the impact of icebreaker activities on student engagement and participation in a senior high school classroom setting. A mixed-methods design was employed, with quantitative data collected through pre- and post-surveys and qualitative data collected through focus group interviews. The sample consisted of students from two sections, one of which incorporated icebreaker activities and the other did not, and the study was conducted over the course of one semester. The findings suggest that icebreaker activities can positively impact student engagement and participation. Quantitative analysis revealed a statistically significant increase in students' self-reported engagement and participation after participating in icebreakers. Qualitative analysis revealed that students felt a greater sense of community and connectedness with their peers, an improved classroom atmosphere and mood, and an increased willingness to participate and engage in class discussions and activities after participating in icebreakers. These findings support the use of icebreaker activities as a tool for promoting student engagement and participation in the classroom. Icebreakers can help students feel more comfortable and connected with their peers, leading to a more positive classroom atmosphere and increased willingness to participate. Additionally, icebreakers can provide opportunities for students to develop important social skills such as communication and teamwork. This study provides valuable insights into the potential benefits of incorporating icebreaker activities into classroom settings. Future research should explore the effectiveness of different types of icebreaker activities and their impact on various student outcomes, as well as factors that may influence the effectiveness of icebreakers such as class size and student demographics.